Colombia: guerra, poder y negociación - Salazar, Boris (Sociedad y Economía, 2002)
Power is what is at stake in the armed conflict of Colombia. The peace talks, recently broken off, between Government and Farc belied the half-disclosed efforts toward military strengthening in which both parties were actively engaged. There is today a new strategic situation that allows to expect that the guerrilla consent to forgo the use of arms and to dilute its military organization: that would be a maximal relative allowance for a maximal relative gain —to take a partial share in the new allotment of the incoming power. A reasonable proposal for negotiation has to start by pondering the mutual benefits of both parties and excluding from the talks the products of depredation. The idea of buying up the violent actors is a way of setting forth the substantiation of this type of approach.